The batterer a psychological profile - Dutton, Donald G. 1943-; Golant, Susan K. (Basic Books, a division of HarperCollins Publishers, 1995)
A study based on interviews with more than seven hundred abusive men offers a psychological profile that provides insight into such figures as O.J. Simpson and Joel Steinberg and identifies the triggers for abusive behavior.